New Species of Distatrix Mason, 1981 (Hymenoptera: Braconidae) from Brazil, with biological notes - Rodrigues, Elizabeth Moreira; Penteado-Dias, Angélica Maria; Dias, Manoel Martins (Zootaxa, 2023)
A new species of the genus Distatrix Mason, 1981 (Hymenoptera: Braconidae) from Brazil is described and illustrated. This parasitoid was reared from larvae of Argyrotome paraguayaria Schaus, 1927 (Lepidoptera: Geometridae: Palyadini), feeding on Myrsine umbellata Mart. (Primulaceae). This is the first record of parasitism in the genus.